Kidney Physiology in Pregnancy (International Journal of Food and Nutritional Sciences, 2022)
A remarkable orchestration of physiologic changes occurs throughout pregnancy. The kidneys are major contributors to the changes in the environment for the pregnant woman and foetus as a result of the changing hormonal milieu of pregnancy. Practically every facet of kidney function is affected by the functional effects of pregnancy on renal physiology. As serum creatinine, urea, and uric acid concentrations fall, the glomerular filtration rate rises by 50%. Lower osmolality and serum sodium levels are the result of reduced antidiuretic hormone and thirst thresholds. Despite an increase in intravascular capacity of 30% to 50% by the second trimester, blood pressure decreases by about 10 mmHg. The renin-aldosterone-angiostensin system is activated as a result of the decrease in systemic vascular resistance, which is multifactorial and partly due to hyposensitivity to vasoactive hormones. A rise in serum aldosterone causes a net sodium gain of about 1000 mg. The pregnant woman is protected from hypokalemia by a concurrent increase in progesterone. Up to 80% of women experience physiologic hydronephrosis, and the kidneys lengthen and enlarge. Understanding these significant changes in kidney physiology during pregnancy will be provided by this review, which is essential in providing care for pregnant patients.